PEMBELAJARAN DALAM JARINGAN DAN MINAT BELAJAR TERHADAP HASIL BELAJAR SISWA SMPN 46 KONAWE SELATAN - Dedyerianto, Dedyerianto; Anggrestiani, Yuli (UIN Imam Bonjol Padang, 2023)
The research aims to determine the effect of online learning and interest in learning on student learning outcomes at SMPN 46 Konawe Selatan. The method used in this research is a survey method with a quantitative approach. The population in this study were all students in grades VII and VIII even semester, totaling 60 students, for the 2020/2021 academic year, the sample selection was carried out using a multistage random sampling technique, namely a combination of simple random sampling and stratified random sampling, after selecting the sample, 49 students were selected .Learning data in the network and learning interest were obtained from questionnaires, while data collection on students' mathematics learning outcomes was taking test scores. The data analysis technique in this study used multiple linear regression analysis. The results showed that online learning and interest in learning had an effect on students' learning outcomes in mathematics, with a contribution of 12.7% while the remaining 87.3% was influenced by other variables outside those studied. The results of this study also show that students' mathematics learning outcomes have a mastery level of learning outcomes of 71.42%, with students' mathematics learning outcomes included in the medium category.